Efficacy of adjunctive treatment with trimetazidine for fragmented QRS among patients with ischemic heart failure: a propensity score match analysis - Kanat, Selçuk; Şensoy, Barış (The European Research Journal, 2019)
Objectives: Fragmented QRS (fQRS) is an indicator of nonhomogeneous ventricular activity caused by myocardial ischemia and fibrosis. The anti-ischemic agent trimetazidine (TMZ) added to pharmacological treatment appears to have positive effects on cardiac parameters of patients with ischemic heart failure. We aimed to investigate the relationship of fQRS with adjunctive TMZ therapy in ischemic HF patients.Methods: Four hundred eighty-nine consecutive ambulatory ischemic patients with heart failure eligible for our study were recruited for the study. A 12-lead electrocardiogram with standard chest and limb leads was used to evaluate the presence of fQRS. Further patients were divided into groups according to adjunctive TMZ treatment and fQRS presence. Confounding factors were adjusted by propensity score matching and multivariate logistic regression analysis.Results: One hundred ninety-seven (40.3%) patients had fQRS on their ECGs and 235 (48.1%) patients were on adjunctive treatment with trimetazidine. Compared to patients without fQRS, patients with fQRS had lower left ventricular ejection fraction (LVEF), higher NYHA classes and more frequent mineralocorticoid receptor antagonist and diuretic usage (p < 0.05). Add-on treatment with TMZ was independently associated with fQRS presence (OR, 0.45; (95% CI, 0.29-0.70); p < 0.0001). Conclusion: According to conventional therapy, adjunctive treatment with TMZ among ischemic heart failure patients can be associated with fQRS in 12-lead ECG independent of LVEF.